CITOMEGALOVIRUS, TOXOPLASMA GONDIí AND HEPATITIS VIRUS TYPES A AND B ANTIBODY SEROPREVAILENCE IN THE GRAVIDLY MALNOURISHED CHILD - Alis Amesty de Valbuena; Monserrat de Villarroel; Adalberto Granados; Robert Andrade; Esperanza Méndez; Marilis Rivero; Leticia Porto; Diana Callejas (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
Child malnutrition has been the subject of numerous investigations for more than two decades trying to understand and explain all the changes that occur as a result of the decrease in protein-caloric intake, Today we know the changes that occur in the immune system and Every day more research is being done on new aspects in this field. However, little is known about the malnutrition response to some infectious diseases such as those caused by Cytomegalovirus (CMV), Hepatitis A Virus and B and toxoplasmosis. In order to know this aspect, a serological study was carried out to investigate antibodies directed against the Hepatitis A and B virus, CMV and Toxoplasma gondii in a population of 64 severely malnourished between 6 and 24 months and compare them with a similar age group. of 35 control children (eutrophic). It was found that for CMV the seroprevalence in the malnourished child was 48.4% compared to 34.22% in the group of control children. Similarly, for Toxoplasma gondii, the percentage of seroprevalence for the malnourished (10.9%) was higher than that of the control group (2.8%). No difference in seroprevalence was found for the Hepatitis A virus in the malnourished and control group, while for the Hepatitis B virus only one malnourished had positive IgM anticore antibodies (indicative of recent infection) and none of the control group. When studying the recent infection for CMV by investigating specific IgM antibodies, it was found that 22% of malnourished patients were newly infected, contrasting with 8.3% of the control group. For Toxoplasmosis, recent infection was demonstrated in 57.1% of cases and there were no cases in the control group. No recent infection was demonstrated in either group for Hepatitis A Virus. The highest percentage of all newly infected patients for both Toxoplasma gondii and CMV corresponded to the age group of 12 to 24 months. These results allow us to conclude that malnutrition is a predisposing factor for early CMV and Toxoplasma gondii infection, that it is acquired predominantly after one year of life and that given the conditions of transient immunodeficiency that malnutrition presents, these infections should be considered when there are clinical conditions such as pneumonia, meningoencephalitis or diarrhea whose etiology by conventional examinations could not be clarified.